ARDCH:adaptive round distributed cluster head scheme for multimedia sensor networks - LI Rui-fang; LI Ren-fa; LUO Juan (Tongxin xuebao)
The node deployment and location-related multimedia data in WMSN were analyzed.Based on the energy ef-ficiency and communication range,an adaptive round distributed cluster head（ARDCH） scheme was proposed.To bal-ance the energy consumption of nodes in WMSN,the cluster headers were selected according to the communication cost and the remaining energy,and the work round of cluster headers were adjusted dynamically by the remaining energy.The multi-channel communication between different clusters was employed in ARDCH to avoid inter-cluster interference.By comparison with other clustering protocols,the simulation results show that ARDCH is more appropriate for WMSN and prolong the life cycle of network.